1990
DOI: 10.1002/elan.1140020308
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microscopic electrode kinetics with electrogenerated chemiluminescence imaging

Abstract: Light produced by the electrogenerated chemiluminescence reaction of luminol in alkaline peroxide was monitored with a sensitive imaging system. The light images were taken to represent the level of microscopically local activity on the electrode surface with a spatial resolution in the submicrometer domain. The temporal resolving capabilities of the imaging system permitted the construction of time‐sequenced images and intensity‐potential profiles, the latter being equivalent to a microscopically local voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Optical techniques based on fluorescence microscopy or electrogenerated chemiluminesence (ECL) provide structural and kinetic information with ∼1 μm resolution. Kuhr et al chemisorbed fluorescent tags to functional groups on carbon fibers and then observed their locations with optical microscopy. Engstrom et al observed ECL at electrochemically active sites on heterogeneous surfaces such as graphite−Kel-F composites and highly ordered pyrolytic graphite (HOPG). STM and AFM provide spatial resolution of a few angstroms and led to the development of scanning electrochemical microscopy (SECM). SECM provides spatial resolution well below 1000 Å and is particularly valuable for studying kinetic heterogeneity. However, SECM, STM, and AFM provide relatively little information about molecular structure of the adsorbates.…”
mentioning
confidence: 99%
“…Optical techniques based on fluorescence microscopy or electrogenerated chemiluminesence (ECL) provide structural and kinetic information with ∼1 μm resolution. Kuhr et al chemisorbed fluorescent tags to functional groups on carbon fibers and then observed their locations with optical microscopy. Engstrom et al observed ECL at electrochemically active sites on heterogeneous surfaces such as graphite−Kel-F composites and highly ordered pyrolytic graphite (HOPG). STM and AFM provide spatial resolution of a few angstroms and led to the development of scanning electrochemical microscopy (SECM). SECM provides spatial resolution well below 1000 Å and is particularly valuable for studying kinetic heterogeneity. However, SECM, STM, and AFM provide relatively little information about molecular structure of the adsorbates.…”
mentioning
confidence: 99%
“…The pioneer works on ECL imaging were conducted by Engstrom et al to visualize the electrode heterogeneity and to characterize electrode kinetics at microscopic scale. [9][10][11][12] The following ECL imaging at arrays of microelectrode exhibited both high sensitivity and high resolution to profile the species over the electrode surface. [13][14][15][16] These important breakthroughs result in an emerging electrochemical imaging approach for parallel measurement of samples, or observation of electrochemical and/or biological events at the regions of interest (ROI), such as uneven cellular effluxes associated with heterogeneous distribution of exocytotic microdomains in cells.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of total electrode current provides only an average picture of electrochemical activity at that electrode, so that inferences about surface heterogeneity extracted mathematically must be based on some assumed geometry of regions having an assigned degree of activity (1,2). Direct observation of the location of electrochemical activity has been accomplished using several techniques, including scanning microreference/auxiliary electrodes to sense local variations in current density (3)(4)(5), iontophoresis to eject electroactive material onto a local region of an electrode surface (6, 7), visualization of electrodeposited polymers (8), photoelectrochemical measurements (9,10), imaging of electrogenerated chemiluminescence (ECL) (11)(12)(13)(14), and monitoring of species in the diffusion layer with a microelectrode (15) as in scanning electrochemical microscopy (SECM) (16)(17)(18). The latter technique has been used not only to locate regions of elec-trochemical activity but also to obtain information regarding the localized chemical reactivity of surfaces (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Information about the local rate of electron transfer on an electrode surface has been obtained in a few instances. For example, we have used ECL imaging to provide information about microscopically local electron-transfer kinetics by imaging luminescence intensity as a function of electrode potential (14). Spatial resolution at the limits of ordinary light microscopy were obtained, and rather subtle differences in electron-transfer characteristics could be observed.…”
Section: Introductionmentioning
confidence: 99%